Beneficial Effect of Pre-Hardening of Elements Manufactured by the SLA Technology - Pszczółkowski, Bartosz; Lemecha, Magdalena; Rejmer, Wojciech; Ligier, Krzysztof; Bramowicz, Mirosław; Zaborowska, Magdalena; Kulesza, Sławomir (Lubricants, 2022)
In this work the effect of preliminary curing on mechanical, physicochemical and tribological properties of SLA (Stereolithography Appearance) manufactured samples is presented. Three preliminary curing times of 5, 10 and 15 s were selected for SLA manufacturing. The materials’ friction, hardness and capacitance values were determined by ball cratering, Brinell method and electrochemical impedance spectroscopy, respectively. The obtained results showed that the mechanical property values changed most significantly after 10 s of preliminary curing, but friction wear and electrochemical capacitance showed greatest change for samples cured for 15 s. This effect may be explained by the domination of elongation of molecular chains in the first 10 seconds of preliminary curing and the gradual increase of branching processes during the next 15 s.